Critical review of reading model and theories in first and second language - Zainal, Zaidah (Faculty of Management and Human Resource Development, 2003)
Reading models have been much discussed by researchers and language practitioners to explain the cognitive processes which occur in a reader's mind. Because reading is a silent and internal process, much is left unknown. In this paper, the writer attempts to critically discuss the different views of reading processes, from the perspectives of first language (L1) and second language (L2). These views are modelled into two classes, the process and componential models, and further divided into three types, the bottom-up, top-down and interactive models..Further discussion of L2 reading is also provided in the light of whether L2 reading is a language or reading problem. To provide further insights into the cognitive processes of a reader, two types of hypotheses commonly used to explain the complexities involved in L2 reading are reviewed, the language interdependence hypothesis and the language threshold hypothesis